Self-love journey through drawing / Dr. Leow Min Hui - Leow, Min Hui (Academy of Language Studies, 2024)
A feeling of appreciation for oneself that promotes physical, mental, and spiritual development is known as self-love. Cultivating self-love is a good way to increase self-esteem and discover inner serenity. Self-love can be incorporated into one’s lifestyle in different ways. When you take good care of your body and health, by getting enough sleep, eating a balanced diet, and engaging in regular exercise, self-love is demonstrated through your efforts to maintain well-being and the value of your life. When you embrace self-compassion through acknowledging your strengths and imperfections, you will stop comparing yourself to others and start accepting yourself as who you are; self-love begins to grow here. For me, finding a good thing in myself is the key to self-love; and I appreciate living with it, enjoy practicing it. To be honest, working equates to racing for fulfilling goals and KPI. A person who loves himself can balance work and life well, but somehow hardly find peace. We occasionally need to “escape” from reality to find peace. The state of peace often reveals our true selves, which cultivates self-love.